Pengaruh Perputaran Kas, Perputaran Piutang dan Leverage (DER) Terhadap Profitabilitas (ROA) Pada Perusahaan Pertambangan yang Terdaftar di BEI 2016-2018 - Elli Frisca Napitupulu; Rendi Andika Ginting; Rini Monika Sinurat; Yemima Nadeak; Friska Darnawati Sitorus (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
In a company always expects high profitability, but that will not be achieved if the operational process does not run well, meaning that the company certainly requires a lot of capital in managing its business. With this we as researchers want to discuss and analyze how "The Effect of Cash Turnover, Accounts Receivable Turnover, and Leverage on Profitability in mining companies listed on the Stock Exchange in the 2016-2018 ". The nature of the research is based on the level of explanation which is to understand the existence of significant between one variable and different variables. Purposive sampling technique is used to examine populations and samples. The population is 48 companies, the sample of 20 companies multiplied by 3 years, the number of observations is 60 samples. Data collection techniques contain assessments obtained through research inferior data collection and sources from the financial statements website. This research was tested in multiple linear regression studies. In carrying out hypothesis testing the data will be tested using classic presumption data. Adjusted R Square 23.1%, it is said that only 23.1% of the profitability variable affects the independent variable. The remaining 76.9% is influenced by other variables. Test results shows that simultaneous cash turnover, accounts receivable turnover, leverage have a significant and significant effect on profitability. Partially cash turnover and leverage have no effect and are not significant on profitability while accounts receivable turnover have a significant and significant effect on profitability